Smart city: A system for measuring noise pollution - Ivan JEZDOVIÄ†; Nevena NEDELJKOVIÄ†; Lazar Å½IVOJINOVIÄ†; BoÅ¾idar RADENKOVIÄ†; Aleksandra LABUS (Smart Cities and Regional Development Journal, 2018)
This paper deals with the development of Smart city services, with the focus on IoT services for measuring the noise pollution. Decreasing noise in the human environment can contribute to increasing the satisfaction of life in the big cities and urban areas where traffic jams are almost inevitable. The aim of this paper is to increase traffic noise awareness and to influence noise reduction through collecting and analyzing the environment data. We have designed, implemented and tested a system for measuring noise pollution, based on Internet of things, web and big data technologies. The system measures and analyses noise level and sends data to the server, where they are further stored, merged and prepared for visualization. As a support to the system, a web and mobile application have been developed. Mobile application enables us to collect large amounts of data from different parts of the city in a quick and efficient. Collection of data can be done by any citizen who has an Android device with installed application. The collected data are stored in the MongoDB. After analyzing data from different parts of the city, we have the ability to create noise maps that indicate the magnitude of the noise pollution for those city blocks. The analyzed data are compared with the legally defined norms and if the norms are not met, the competent authorities are alerted to solve the noise pollution problem.